Perioperative hemostasis : coagulation for anesthesiologists - Marcucci, Carlo Enrique; Schoettker, Patrick (Springer Berlin Heidelberg Imprint: Springer, 2015)
All anesthesiologists are confronted with patients who show bleeding disorders, whether congenital, acquired, or pharmacologically induced. Although many studies, meta-analyses, guidelines, and textbooks have been published on the subject, they mostly cover specific aspects or require a thorough knowledge of hemostasis. The goal of this book is to provide the anesthetist with an overview of hemostasis and the mechanisms underlying bleeding and coagulation in general and to assist in the understanding of specific coagulation disorders as they may occur in the various anesthetic subspecialties. It is hoped that, through the provision of practical information and tools, the book will help residents and trained anesthetists to manage one of the most frustrating challenges that they face: the bleeding patient. A full understanding of coagulation requires a lifelong career, and this book is not intended to replace the consulting hematologist, whose expert opinion should always be sought. The available procoagulant blood products and drugs all have potentially dangerous side-effects; furthermore, in bleeding disorders pitfalls are frequent and a misdiagnosis can have potentially catastrophic consequences. The aim of the editors is thus instead to enhance the collaboration between the disciplines of Anesthesiology and Hematology.